2012
DOI: 10.1371/journal.pone.0051941
|View full text |Cite
|
Sign up to set email alerts
|

Resident Alveolar Macrophages Are Susceptible to and Permissive of Coxiella burnetii Infection

Abstract: Coxiella burnetii, the causative agent of Q fever, is a zoonotic disease with potentially life-threatening complications in humans. Inhalation of low doses of Coxiella bacteria can result in infection of the host alveolar macrophage (AM). However, it is not known whether a subset of AMs within the heterogeneous population of macrophages in the infected lung is particularly susceptible to infection. We have found that lower doses of both phase I and phase II Nine Mile C. burnetii multiply and are less readily c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…In support of our data showing the increased replication of C. burnetii in AMs, it was previously reported that tissue-resident AMs are susceptible to C. burnetii replication in vivo (12). Moreover, human AMs were shown to support C. burnetii replication in culture (11).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In support of our data showing the increased replication of C. burnetii in AMs, it was previously reported that tissue-resident AMs are susceptible to C. burnetii replication in vivo (12). Moreover, human AMs were shown to support C. burnetii replication in culture (11).…”
Section: Discussionsupporting
confidence: 90%
“…Because most of the gene-deficient mice generated thus far were constructed in the C57BL/6 mouse background, we aimed to identify a primary cell that supported the replication of C. burnetii phase II in culture. It is known that C. burnetii infects macrophages and monocytes, with AMs considered the primary target cell of infection (10,12,(19)(20)(21)(22). Thus, we evaluated whether murine AMs from the C57BL/6 mouse strain support the replication of C. burnetii phase II in culture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary target of Coxiella during natural infection is alveolar macrophages [32,[41][42][43]. The organism can subsequently disseminate to colonize and replicate in resident macrophages of different tissues and organs [44].…”
Section: Making a Home In Host Cellsmentioning
confidence: 99%
“…The potential cellular targets for immune modulation to treat PcP include CD4 T cells, CD8 T cells, regulatory T cells, neutrophils, macrophages, and epithelial cells (24,25). Macrophages offer a novel approach to cell therapy in the treatment of infection, especially in the immunosuppressed hosts, but require additional investigation (26)(27)(28)(29)(30)(31). There are relatively few reports concerning macrophage polarization and the resulting antifungal and anti-inflammatory activity as a potential treatment approach for fungal infections (12,32,33).…”
mentioning
confidence: 99%